Beyond compensation: A cross-sectional study on the psychological and occupational impact of unjust dismissal in Colombia - Galindo Ángel, Guillermo Alfonso (Acciones e Investigaciones Sociales, 2025)
Colombian legislation provides for a fixed compensation for unjustified dismissal, but its capacity to repair comprehensive damage is questioned. This study empirically investigates the impact of unjustified dismissal on psychological well-being and labor reintegration prospects of workers in Colombia, examining the mediating role of perceived injustice. A cross-sectional study was conducted with a sample of 250 Colombian workers who lost their jobs in the last 24 months, classified into three groups: unjustified dismissal (n=85), dismissal with just cause (n=75), and termination due to restructuring (n=90). Validated scales were used to measure psychological distress (K-10), perceived injustice, labor reintegration difficulty, and duration of unemployment. Workers who were dismissed unjustifiably reported significantly higher levels of psychological distress (F(2, 247) = 18.23, p < .001) and greater labor reintegration difficulty compared to other groups. Perceived injustice proved to be a robust predictor of psychological distress (β = 0.45, p < .001) and partially mediated the relationship between type of dismissal and distress. The findings provide empirical evidence that legal compensation is insufficient to mitigate the severe psychological and occupational impact of unjustified dismissal.
Keywords: Unjustified dismissal; Organizational justice; Psychological well-being; Occupational health; Labor legislation; Colombia